Early stage (IA-IB) primary carcinoma of the fallopian tube: case-control comparison to adenocarcinoma of the ovary - Vaysse, Charlotte (Asian Society of Gynecologic Oncology; Korean Society of Gynecologic Oncology and Colposcopy, 2011)
OBJECTIVE: Early stage primary carcinoma of the fallopian tube (PCFT) is an uncommon condition when strict criteria are applied. The aim of this study was to compare the outcome stage IA-IB PCFT to a matched group of ovarian cancer (OC). METHODS: Between 1990 and 2008, 32 patients with stage IA-IB of PCFT were recorded in the database of three French Institutions. A control group of patients with OC was constituted. RESULTS: Eleven eligible PCFT cases and 29 OC controls fulfilled the stringent inclusion criteria. Median follow-up was 70.2 months. Five-year overall survival was 83.3% (95% confidence interval [CI], 27.3 to 97.5) for PCFT and 88.0% (95% CI, 66.9 to 96.0) for OC (p=0.93). In the subgroup of patients with grade 2-3, the outcome was similar in PCFT compared to OC patients (p=0.75). Five-year relapse-free survival was respectively 62.5% (95% CI, 22.9 to 86.1) and 85.0% (95% CI, 64.6 to 94.2) in the PCFT and OC groups (p=0.07). In the subgroup of patients (grade 2-3), there was no difference between PCFT and OC (p=0.65). CONCLUSION: The findings did not reveal any difference in prognosis between early stage of PCFT and OC when grade is taken into account. Management of PCFT should mirror that of ovarian carcinoma.